THE INFLUENCE OF ORGANIZATIONAL CULTURE AND TRANSFORMATIONAL LEADERSHIP ON PERFORMANCE THROUGH WORK MOTIVATION AS AN INTERVENING VARIABLE (CASE STUDY ON PERMANENT PRIVATE JUNIOR HIGH SCHOOL TEACHERS IN BOGOR CITY, SPECIFICALLY WEST BOGOR - Dian Ekawati Br. Sitepu; Nancy Yusnita; Herdiyana (Journal of Social and Economics Research, 2024)
This study aims to analyze the influence of organizational culture and transformational leadership on teacher performance through work motivation as an intervening variable among permanent private junior high school teachers in Bogor City, specifically West Bogor, with accreditation status "A." The results indicate that organizational culture does not have a significant direct influence on teacher performance. However, there is a positive influence of organizational culture on work motivation. Transformational leadership also does not directly affect teacher performance. On the other hand, transformational leadership positively influences work motivation. Work motivation has a positive effect on teacher performance. Furthermore, there is an indirect influence of organizational culture on teacher performance through work motivation. The indirect influence of transformational leadership on teacher performance through work motivation is also significant. This study concludes that work motivation plays a crucial role as an intervening variable in improving teacher performance. Therefore, enhancing organizational culture and effective transformational leadership can support better teacher performance by considering work motivation as a key factor.